The Relationship Between Parental Factors and Dental Caries in Children - Rezki, Sri; Nurhayati, Putri; Pawarti, Pawarti; Fathiah, Fathiah; Susatyo, Jojok Heru; Maryani, Yeni; Halimah, Halimah (Ahmar Metastasis Health Journal, 2025)
Based on the 2018 Basic Health Research (Riskesdas), 93% of preschool-aged children in Indonesia experience dental caries, indicating the crucial role of parents in establishing oral health habits from an early age. This study aimed to determine the relationship between caregiving factors and dental caries in children. An analytic cross-sectional survey design was used, conducted at the Posyandu in Sekip Lama Village under UPT Puskesmas Singkawang Tengah I, with a population of 84 participants selected through a total sampling technique. Research instruments included a caregiving behavior questionnaire, the child’s age, the number of the child’s teeth, the caregiver’s educational background and occupation, as well as the caries index; data were analyzed using the Spearman correlation test. The results showed that most parents had caregiving behavior in the adequate category (69.3%), with an average behavior score of 18.71 ± 4.5; children had an average dmf-t index of 6.08 ± 4.9, at ages 12–60 months, and an average number of teeth of 17 ± 4.5. The Spearman test revealed a significant relationship between the severity of dental caries and the child’s age, the number of teeth, the caregiver’s educational level, and caregiving behavior (p < 0.05). It can be concluded that caregiving factors play an important role in children’s oral health conditions, and parents are encouraged to be more proactive in fostering good oral hygiene habits from an early age.